Gas permeation through graphdiyne-based nanoporous membranes - Zhihua Zhou; Yongtao Tan; Qian Yang; Achintya Bera; Zecheng Xiong; Mehmet Yagmurcukardes; Minsoo Kim; Yichao Zou; Guanghua Wang; Artem Mishchenko; Ivan Timokhin; Canbin Wang; et al. (Nature Communications, 2022)
2D nanoporous membranes are predicted to provide highly selective gas transport in combination with extreme permeance. Here authors demonstrate gas separation performance and transport mechanisms through membranes of graphdiyne, a quasi 2D material with a graphene-like structure.